(untitled) (Lundiana: International Journal of Biodiversity, 2009)
A survey of ectoparasites of the Laughing Dove (Streptopelia senegalensis Linnaeus, 1766) was carried out in Zaria, Nigeria, to determine the prevalence, intensity and mean intensity of infestation. A total of 382 (231 males and 151 females) doves trapped from different locations in Zaria, Nigeria, were examined through plumage brushing. Eighty-eight (23.0%) of the birds were infested by the following six species of ectoparasites: lice – 32 (8.4%) Menopon gallinae Linnaeus, 1758, 37 (9.7%) Columbicola columbae Linnaeus, 1758, and 18(4.7%) Goniodes sp.; flies – 19 (5.0%) Pseudolynchia canariensis Macquart, 1840; ticks – 12 (3.1%) Argas persicus Oken, 1818; and mite: 1 (0.23%) Dermanyssus gallinae (Degeer, 1778). The frequency of single infestations (59 – 15.4%), was higher than that of double (27 – 7.1%) and triple (2 – 0.52%) infestations, though the difference was not statistically significant (p > 0.05). The males had a higher prevalence (55 – 23.8%) than the females (33 – 21.9%). However, this difference was also not significant (p > 0.05). Ectoparasites were collected from the birds through out the year, with highest prevalence (60.0%) in November. The difference between the prevalence of ectoparasites in the wet (23.5%) and the dry seasons (22.6%) was also not significant (p > 0.05). The implications and significance of the results are discussed.